Implementasi Model Prototype untuk Perancangan Sistem Informasi Project Monitoring Berbasis Web - Pratiwi, Rolita; Kholil, Ishak (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
PT. Shuba Mitra Solusi is a business in the form of a limited liability company or PT, with a digital agency type of business. The company routinely receives projects from clients within a specified processing time. The large number of projects being carried out at the same time often makes the team overwhelmed, especially the target completion time. The project stages carried out are planning, work, monitoring and evaluation. Obstacles often faced by companies are that many team members report the results of their work manually so that the project leader does not update the information, team work targets are sometimes missed due to somewhat hampered coordination in reporting, team members do not know the next work after the work is completed, difficulty knowing progress of work carried out by the project team. Such obstacles mean that work plans and targets are not in accordance with initial planning, which results in delays in reporting project progress to clients by the project leader. The Project Monitoring Application Prototype that the author proposes tries to provide a solution as a support system to make it easier for teams to report work progress using the task menu and project menu. This facility also makes it easier to find solutions if there are problems or errors within the team, making the coordination and repair process easier. The application of this application at PT Shuba Mitra Solusi is to make it easier for the team to make work reports, provide information on the status of the work being done, and make it easier for leaders to monitor ongoing projects.